PETROGRAPHIC CHARACTERISTICS OF SELECTED TERTIARY COALS FROM WESTERN INDONESIA ACCORDING TO THEIR GEOLOGICAL ASPECTS - Binarko Santoso (Indonesian Mining Journal, 2017)
Selected Tertiary coals from the western part of Indonesia (Sumatera, Kalimantan and Java) indicate similarities and differences in type and rank characteristics. These coals reflect their geological setting, particularly for intrusive and stratigraphic aspects. Type and rank of the coals were assessed by petrographic examination. The coals are mainly dominated by vitrinite, common liptinite and rare inertinite and mineral matter. Vitrinite macerals are dominated detrovitrinite and telovitrinite. Resinite, cutinite and suberinite are the dominant liptinite macerals in the coals. Inertinite macerals in the coals consist of semifusinite, sclerotinite and inertodetrinite. The type differences largely reflect climatic influence and differences in peat conditions. In spite of short geological history, the coals exhibit variable vitrinite reflectances. The high vitrinite reflectance of the coals is a result of higher regional coalification levels in the basins associated with greater cover and effects of igneous intrusions.